EFEKTIVITAS LAYANAN KONSELING KELOMPOK DENGAN PENDEKATAN RATIONAL EMOTIVE BEHAVIOR THERAPY UNTUK MEREDUKSI KECENDERUNGAN SELF-INJURY PADA GENERASI Z - Putri, Nadila Desrani; Anni Suprapti; MT Afriwilda (UNIVERSITAS BENGKULU, 2025)
This study aimed to prove the effectiveness of group counseling using the Rational Emotive Behavior Therapy (REBT) approach in reducing self-injury tendencies among Generation Z. The research employed an experimental method with a two-group pre-test post-test control design. The population of the study consisted of eighth-grade students at SMP Negeri 5 Bengkulu City. The sample included 10 students, divided into two groups: 5 students in the experimental group and 5 students in the control group, selected through purposive sampling. Data analysis was conducted using the t-test. The results of the t-test showed a significant difference in self-injury tendencies between Generation Z adolescents who received group counseling with the REBT approach and those who received group counseling without the REBT approach. Therefore, it was concluded that group counseling with the Rational Emotive Behavior Therapy approach was effective in reducing self-injury tendencies among Generation Z. Keywords: group counselling, self-injury, rational emotive behavior therapy